1997
DOI: 10.1111/j.1365-2028.1997.083-89083.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability in the structure of a tropical forest

Abstract: This study examines spatial and temporal variation in the forest structure of the Kibale National Park, Uganda by contrasting tree density, tree size, and forest composition among four areas each separated by less than 15 km, and by quantifying changes in the composition of one of these forests over a 20‐year period. Densities of some tree species differed markedly between sites, and some species common at one location were absent at others. Monthly phenological monitoring demonstrated that it was not uncommon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 24 publications
5
95
0
2
Order By: Relevance
“…<20dbh) in this zone was due to the problem of disturbance whereby the matured trees were removed for the purpose of charcoal burning, fuel wood collection, fruit collection and timber harvesting (personal observation of the site). According to , Chapman et al (1997) and Whitmore and Sayer (1992) disturbance through uncontrolled logging were considered as the main factors destroying mature and young trees. However, the buffer and strict nature reserve zone, dipcted the highest distribution of mature trees than younger saplings and seedlings trees.…”
Section: Discussionmentioning
confidence: 99%
“…<20dbh) in this zone was due to the problem of disturbance whereby the matured trees were removed for the purpose of charcoal burning, fuel wood collection, fruit collection and timber harvesting (personal observation of the site). According to , Chapman et al (1997) and Whitmore and Sayer (1992) disturbance through uncontrolled logging were considered as the main factors destroying mature and young trees. However, the buffer and strict nature reserve zone, dipcted the highest distribution of mature trees than younger saplings and seedlings trees.…”
Section: Discussionmentioning
confidence: 99%
“…Also Chapman et al (1997) found variation in vegetation between the southern and northern parts of Kibale National Park. Differences in plant communities can influence the community structure of herbivorous insects (Crist et al 2006, Savilaakso et al 2009, Whitham et al 2006.…”
Section: Spatial Variation In Community Compositionmentioning
confidence: 99%
“…In Kibale, the climate is relatively stable but the microclimate can vary locally (Savilaakso et al 2009). Chapman et al (1997) found that in Kibale National Park average temperatures rise and precipitation decreases from north to south. Local climate changes also temporally, mostly because of unpredictable timing of the rainy seasons (Chapman et al 2005).…”
Section: Spatial Variation In Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the highest number of species can only be conserved when complementary areas are included in the conservation plan (Howard et al 1998). The maintenance of the high diversity of Budongo, being an isolated forest with no immediate source of additional forest species, may be more attributed to the existence of all stages of the succession gradient (Richardson-Kageler 2004;Shea et al 2004) than acquisition of more forest species from elsewhere, which, additionally, often takes a long time (Chapman et al 1997). Hence, if reforestation of Budongo Forest Reserve would continue to the extent that the woodland areas would be lost, the biodiversity of the reserve would probably decrease.…”
Section: The Effect Of Continuing Reforestation On the Biodiversity Omentioning
confidence: 99%